Validity of the Alarm Point in Intraoperative Neurophysiological Monitoring of the Spinal Cord by the Monitoring Working Group of the Japanese Society for Spine Surgery and Related Research: A Prospective Multicenter Cohort Study of 1934 Cases. Issue 20 (15th October 2021) - Takahashi, Masahito; Imagama, Shiro; Kobayashi, Kazuyoshi; Yamada, Kei; Yoshida, Go; Yamamoto, Naoya; Ando, Muneharu; Kawabata, Shigenori; Kanchiku, Tsukasa; Fujiwara, Yasushi; Taniguchi, Shinichirou; Iwasaki, Hiroshi; et al.
Abstract : The alarm point of intraoperative neurophysiological monitoring of the spinal cord by the Working group of the Japanese Society for Spine Surgery and Related Research (JSSR) was evaluated. The sensitivity and specificity of each high-risk surgery were sufficient. Meanwhile, applying the JSSR alarm point for common surgery potentially needed attention. Abstract : Study Design: Prospective multicenter cohort study. Objective: The aim of this study was to validate an alarm point of intraoperative neurophysiological monitoring () formulated by the Monitoring Working Group (WG) of the Japanese Society for Spine Surgery and Related Research (JSSR). Summary of Background Data: The Monitoring WG of the JSSR formulated an alarm point of IONM using transcranial electrical stimulation-muscle motor evoked potentials (Tc(E)-MEPs) and has conducted a prospective multicenter study. The validity of the JSSR alarm point of ≥ 70% decreased in Tc(E)-MEPs for each high-risk surgery and any other spine surgeries has not been verified. Methods: Patients who underwent spine and spinal cord surgery with IONM in 16 Japanese spine centers in the Monitoring WG of the JSSR from 2017 to 2018 were enrolled. The patients were divided into the high-risk surgery group (Group HR) and the common surgery group (Group C). Group HR was defined by ossification of the posterior longitudinal ligament (OPLL), spinal deformity, and spinal cord tumor. Group C was classified as other spine surgeries. The alarm point was defined as a ≥70% decrease in the Tc(E)-MEPs. Results: In Group HR, the sensitivity and specificity were 94.4% and 87.0%, respectively. In Group C, the sensitivity and specificity were 63.6% and 91.9%. The sensitivity in Group C was statistically lower than that in Group HR ( P  < 0.05). In Group HR, the sensitivity and specificity in OPLL were 100% and 86.9%, respectively. The sensitivity and specificity in spinal deformity were 87.5% and 84.8%, respectively, and the sensitivity and specificity in spinal cord tumors were 92.9% and 89.9%, respectively. The sensitivity and specificity in each high-risk surgery showed no significant difference. Conclusion: The alarm point of IONM by the Monitoring WG of the JSSR appeared to be valid for each disease in Group HR. Meanwhile, applying the JSSR alarm point for Group C potentially needed attention. Level of Evidence: 3